A Complete Data Set of Equatorial Projections of Saturn's Energetic Neutral Atom Emissions Observed by Cassini‐INCA. Issue 6 (3rd June 2021) - Bader, A.; Kinrade, J.; Badman, S. V.; Paranicas, C.; Constable, D. A.; Mitchell, D. G.
Abstract: Observations of energetic neutral atoms (ENAs) are a useful tool for analyzing ion and neutral abundances in planetary magnetospheres. They are created when hot plasma, originating for example from magnetic reconnection sites, charge‐exchanges with the ambient neutral population surrounding the planet. The motion of ENAs is not governed by the magnetic field, allowing remote imaging. During the Cassini mission, the Ion and Neutral CAmera (INCA) of the Magnetosphere Imaging Instrument (MIMI) collected vast amounts of hydrogen and oxygen ENA observations of Saturn's magnetosphere from a variety of different viewing geometries. To enable investigations of the morphology and dynamics of Saturn's ring current, it is useful to re‐bin and re‐project the camera‐like views from the spacecraft‐based perspective into a common reference frame. We developed an algorithm projecting INCA's ENA observations into a regular grid in Saturn's equatorial plane. With most neutrals and ions being confined into an equatorial rotating disc, this projection is quite accurate in both spatial location and preservation of ENA intensity, provided the spacecraft is located at large enough elevations. Such projections were performed for all INCA ENA data from the Cassini Saturn tour; the data are available for download together with a Python routine flagging contaminated data and returning detailed spacecraft geometry information. The resulting data set is a good foundation for investigating for example the statistical properties of Saturn's ring current and its complicated dynamics in relation to other remote and in situ observations of, for example, auroral emissions and magnetotail reconnection events. Plain Language Summary: Energetic neutral atom (ENA) observations contain useful information about ion and neutral abundances in planetary magnetospheres. They are created when energetic ions transfer their charge onto particles in a planet's neutral exosphere, leaving an energetic neutral with the original ion's energy and direction of motion. ENAs can be observed remotely, as their motion is no longer determined by the planetary magnetic field. Cassini's Ion and Neutral CAmera (INCA) obtained such remote observations of Saturn's magnetosphere for more than a decade. To simplify large‐scale analyses of this vast data set, it is useful to re‐bin and re‐project all observations into a common reference frame, as the perspective of the imagery varies significantly depending on Cassini's position and attitude. Most ions and neutrals are confined to Saturn's equatorial plane due to the planet's rapid rotation, making this the source region of most ENAs and an ideal common reference frame. We developed an algorithm projecting all of INCA's ENA observations into a regular grid in Saturn's equatorial plane, creating a clean and easy‐to‐use data set which can be utilized to investigate the morphology and dynamics of Saturn's ring current and its relation to, for example, ultraviolet auroral emissions and magnetic reconnection in the nightside magnetosphere. Key Points: All Ion and Neutral CAmera observations of energetic neutral atoms from the Cassini Saturn tour are projected into Saturn's equatorial plane The full set of projections in the form of daily .fits files is accessible online for further scientific analyses Different types of data contamination are identified and projections are flagged accordingly when loaded with the Python routine provided